2018
DOI: 10.16992/asos.14457
|View full text |Cite
|
Sign up to set email alerts
|

Beslenme Ve Di̇yeteti̇k Bölümü Erkek Öğrenci̇leri̇nde Ortoreksi̇ya Nervoza Eği̇li̇mi̇ni̇n Beli̇rlenmesi̇

Abstract: Amaç: Ortoreksiya nervoza (ON) sağlığın korunması, iyileştirilmesi, hastalığın tedavisi veya ağırlık kaybetme gibi amaçlarla katkısız, işlenmemiş besinleri tüketme eğilimin görüldüğü "sağlıklı beslenme takıntısı" olarak tanımlanmaktadır. Ortorektikler, mükemmelliğe ulaşma çabalarından ötürü diyetlerini giderek kısıtlama eğilimi göstermekte, bu kişilerde malnutrisyon gelişebilmektedir. Bu araştırma Beslenme ve Diyetetik Bölümü'nde eğitimi alan kız öğrencilerin ON eğilimini belirlemek amacıyla yapılmıştır. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…Another study including school of health students reported mean points were 26.95 ± 5.11 18 . Garipoğlu et al ( 2019) stated that 76.7% of female students attending the nutrition and dietetics department had orthorectic tendencies 19 . Another study performed with male students from the nutrition and dietetic department identified that 70.6% displayed orthorectic tendencies 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Another study including school of health students reported mean points were 26.95 ± 5.11 18 . Garipoğlu et al ( 2019) stated that 76.7% of female students attending the nutrition and dietetics department had orthorectic tendencies 19 . Another study performed with male students from the nutrition and dietetic department identified that 70.6% displayed orthorectic tendencies 20 .…”
Section: Resultsmentioning
confidence: 99%
“…normal BMI 24 . In our current study, it is thought that the reason for the lower mean of BMI is due to the university population of the younger age group.…”
Section: Discussionmentioning
confidence: 99%
“…Social media is at the same time an electronic form of communication that enables users to produce and use content, providing social interaction, and appointment 6 . Communication of individuals born in the digital world (ages [15][16][17][18][19][20][21][22][23][24] takes place on social media or social networks 7 . It was found that 13% of young people in Turkey spent more than six hours on social media, 86% of them connect to social media at least once a day 8 .…”
Section: Introductionmentioning
confidence: 99%
“…ORTO-15 testinden alınan ortalama puan 37,30±4,56'dır. Bu çalışmada Beslenme ve Diyetetik erkek öğrencilerinin ON yatkınlığı boya, ağırlığa ve BKİ'ye göre değişmemiştir (Arusoğlu, 2018). Üniversite öğrencilerinde yapılan başka bir çalışmada, ON görülme durumu ile BKİ değerleri arasında anlamlı bir ilişki bulunmamıştır (Yabancı, 2017).…”
Section: Tartışma Ve Sonuçunclassified
“…Sağlık personeli olan ve olmayan bireylerde ON sıklığını araştırmak amacıyla yapılan bir çalışmada, sağlık personeli olan katılımcıların %29,10'u sağlık personeli olmayanların ise %42,20'si sigara içmektedir ve sigara kullanımı ile ON arasında anlamlı bir ilişki bulunamamıştır (Ergin, 2014). Beslenme ve Diyetetik bölümü erkek öğrencileri dâhil edilerek yapılan bir çalışmada da aynı şekilde sigara içme durumu ile ortorektik eğilim arasında anlamlı bir ilişki belirlenmemiştir (Arusoğlu, 2018).…”
Section: )unclassified